Induction of protective immune responses at respiratory mucosal sites - Park, Seok-Chan; Wiest, Matthew J.; Yan, Vivian; Wong, Pamela T.; Schotsaert, Michael (Human vaccines & immunotherapeutics, 2024)
Many pathogens enter the host through mucosal sites. Thus, interfering with pathogen entry through local neutralization at mucosal sites therefore is an effective strategy for preventing disease. Mucosally administered vaccines have the potential to induce protective immune responses at mucosal sites. This manuscript delves into some of the latest developments in mucosal vaccination, particularly focusing on advancements in adjuvant technologies and the role of these adjuvants in enhancing vaccine efficacy against respiratory pathogens. It highlights the anatomical and immunological complexities of the respiratory mucosal immune system, emphasizing the significance of mucosal secretory IgA and tissue-resident memory T cells in local immune responses. We further discuss the differences between immune responses induced through traditional parenteral vaccination approaches vs. mucosal administration strategies, and explore the protective advantages offered by immunization through mucosal routes.